Explicit substitions and all that - Ayala Rincón, Mauricio; Muñoz, César (Revista Colombiana de Computación, 2000)
Explicit substitution calculi are extensions of the calculus where the substitution mechanism is internalized into the theory. This feature makes them suitable for implementation and theoretical study of logic based tools as strongly typed programming languages and proof assistant systems. In this paper we explore new developments on two of the most successful styles of explicit substitution calculi: the λσ- and λsе-calculi. Keywords: Explicit substitution, higher order uni cation, lambda-calculi, type and rewriting theory.